2015
DOI: 10.1785/0120150091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seabed Surface Rupture Versus Buried Rupture on Tsunami Wave Modeling: A Case Study for the 2011 Tohoku, Japan, Earthquake

Abstract: Goda, K. (2015). Effects of seabed surface rupture versus buried rupture on tsunami wave modeling: A case study for the 2011 Tohoku, Japan earthquake. Bulletin of the Seismological Society of America, 105 (5) Abstract Parametric investigations of tsunami wave modeling are performed to discuss an important issue related to the sensitivity of tsunami simulation results to varied top-edge depths of a shallowly dipping fault plane (seabed surface rupture versus buried fault rupture). Input boundary conditions (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It has been also observed that this filtering effect is less effective for shallower rupture areas. For instance, Goda [] analyzed identical earthquakes with different fault depths. He noted that shallower earthquakes were associated with sharper seabed deformations patterns.…”
Section: Stochastic Modeling Of Earthquakesmentioning
confidence: 99%
“…It has been also observed that this filtering effect is less effective for shallower rupture areas. For instance, Goda [] analyzed identical earthquakes with different fault depths. He noted that shallower earthquakes were associated with sharper seabed deformations patterns.…”
Section: Stochastic Modeling Of Earthquakesmentioning
confidence: 99%
“…In the above-mentioned procedure for calculating the water surface elevation, the hydrodynamic response of seawater is not accounted for. Caution needs to be exercised when modelling tsunamigenic earthquakes with major asperities on a gently dipping fault plane at a shallow depth (applicable to the Nankai -Tonankai earthquake), because large peak vertical deformation is generated along the top edge of the dipping fault (Goda 2015) as a result of the assumption of elastic behaviour of the rock encoded in the Okada (1985) solutions. In reality, strongly non-linear (plastic) deformation occurs, which is typically not accounted for in tsunami simulations: instead, the seabed deformation calculated from the Okada (1985) equations is used directly as an input sea surface condition in the tsunami simulation.…”
Section: Offshore Tsunami Resultsmentioning
confidence: 99%
“…Global coupled ocean‐atmosphere numerical models are commonly used to determine offshore sea state conditions (e.g., Janssen & Bidlot 2018). Further numerical models and/or theoretical/empirical relations (e.g., Burcharth & Hughes, 2000; Goda, 2015; Kang et al., 2020) are then used to calculate shoaling and runup processes to estimate wave height and period at the coast. These models and theoretical/empirical relations assume that conditions are stationary and are commonly calibrated with wave climatology measured at the coast for at least a few months.…”
Section: Introductionmentioning
confidence: 99%